Effects of aqueous extract of Fadogia agrestis stem in alloxan-induced diabetic rats - Musa T. Yakubu; Olalekan B. Ogunro (Bangladesh Pharmacological Society, 2014)
Aqueous extract of Fadogia agrestis stem at the doses of 18, 36, and 72 mg/kg body weight was investigated for antidiabetic activity in alloxan-induced diabetic rats. The results revealed that the administration of alloxan significantly increased (p<0.05) the levels of blood and hepatic glucose, serum urea, creatinine, albumin, total cholesterol, triacylglycerol, low-density lipoprotein cholesterol, atherogenic index and very low-density lipoprotein cholesterol whereas the organ/body weight ratio, activity of hexokinase, levels of high-density lipoprotein cholesterol, packed cell volume and hemoglobin reduced significantly. In contrast, all the doses of the extract significantly reversed the levels of these biomolecules/biochemical parameters. These reversals, however, did not compare well with their respective control values by the end of exposure period. Overall, the aqueous extract of F. agrestis stem showed promise as an antidiabetic agent.